S SaltyPoro New member Joined Nov 6, 2017 Messages 15 Nov 15, 2017 #1 I keep getting this equation wrong ^{x + 3}/_{4} + ^{x - 1}/_{4} = 1 This is my working out: 4(x+3) + 4(x-1) = 1 4x+12 + 4x-4 = 1 4x + 4x = 1 + 4 - 12 8x = -7 I'm pretty sure I'm doing something wrong but I don't know where.

I keep getting this equation wrong ^{x + 3}/_{4} + ^{x - 1}/_{4} = 1 This is my working out: 4(x+3) + 4(x-1) = 1 4x+12 + 4x-4 = 1 4x + 4x = 1 + 4 - 12 8x = -7 I'm pretty sure I'm doing something wrong but I don't know where.

tkhunny Moderator Staff member Joined Apr 12, 2005 Messages 10,448 Nov 15, 2017 #2 SaltyPoro said: I keep getting this equation wrong ^{x + 3}/_{4} + ^{x - 1}/_{4} = 1 This is my working out: 4(x+3) + 4(x-1) = 1 4x+12 + 4x-4 = 1 4x + 4x = 1 + 4 - 12 8x = -7 I'm pretty sure I'm doing something wrong but I don't know where. Click to expand... Not clear what this is. \(\displaystyle \dfrac{x+3}{4} + \dfrac{x-1}{4} = 1\)? Is that it? \(\displaystyle x + \dfrac{3}{4} + x - \dfrac{1}{4} = 1\)? Or is that it? In any case, multiply EACH TERM (both sides of the equation) by 4 and simplify. One term at a time.

SaltyPoro said: I keep getting this equation wrong ^{x + 3}/_{4} + ^{x - 1}/_{4} = 1 This is my working out: 4(x+3) + 4(x-1) = 1 4x+12 + 4x-4 = 1 4x + 4x = 1 + 4 - 12 8x = -7 I'm pretty sure I'm doing something wrong but I don't know where. Click to expand... Not clear what this is. \(\displaystyle \dfrac{x+3}{4} + \dfrac{x-1}{4} = 1\)? Is that it? \(\displaystyle x + \dfrac{3}{4} + x - \dfrac{1}{4} = 1\)? Or is that it? In any case, multiply EACH TERM (both sides of the equation) by 4 and simplify. One term at a time.